2022
DOI: 10.20886/jakk.2022.19.1.63-70
|View full text |Cite
|
Sign up to set email alerts
|

Pola Peningkatan Suhu Udara Berdasarkan Data BMKG Dan Era5 Di Provinsi Sulawesi Tengah

Abstract: Studies on the trend analysis of surface air temperature have never been conducted in Central Sulawesi Province. This study aims to determine changes in the average surface air temperature trend in Central Sulawesi Province period 1981 to 2019. Linear regression analysis is used to identify the trend of temperature changes over a certain period. The results show that the average surface air temperature is significantly increased by 0.015–0.045°C per year (p < 0.05). The results provide the information on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These low values indicated that the three variables fluctuated from year to year, causing difficulties in finding the linear trends. Apart from the findings, theoritically changes in the composition of the atmosphere caused by greenhouse gas emissions, such as carbon dioxide (CO2), methane (CH4), and nitrogen oxides (NOx), affect directly or indirectly climate conditions [10]. The increase in greenhouse gas emissions plays an essential role in increasing the greenhouse effect, which increases the air temperature in the city.…”
Section: Climate Condition and Co2 Emissionsmentioning
confidence: 99%
“…These low values indicated that the three variables fluctuated from year to year, causing difficulties in finding the linear trends. Apart from the findings, theoritically changes in the composition of the atmosphere caused by greenhouse gas emissions, such as carbon dioxide (CO2), methane (CH4), and nitrogen oxides (NOx), affect directly or indirectly climate conditions [10]. The increase in greenhouse gas emissions plays an essential role in increasing the greenhouse effect, which increases the air temperature in the city.…”
Section: Climate Condition and Co2 Emissionsmentioning
confidence: 99%
“…An increase in air temperature has a significant relationship with natural conditions, development activities and human life patterns (comfort index) [1]. The limited number of meteorological and climatological stations in observing air temperature in the field causes less even air temperature information provided, therefore remote sensing technology is an alternative solution that can be used to observe air temperature evenly for all regions [2].…”
Section: Introductionmentioning
confidence: 99%